Pelatihan Pemasaran Digital untuk Produk Pertanian - Fadjeri, Akhmad; Fersellia, Fersellia; Lutfiyani, Anisa; Anggoro, Tri; Muflih, Ghufron Zaida; Fachri, Fahmi; Wahyuningsih, Endang (Abdibaraya, 2025)
This research aims to evaluate the effectiveness of a digital marketing training program for farmers in Tlogopragoto Village, Kebumen District, focusing on improving their ability to market agricultural products, specifically chili. The study adopts a descriptive qualitative approach, utilizing data collection methods such as direct observation, semi-structured interviews, questionnaires, and documentation. The training, conducted on November 2, 2024, at the Roda Tani chili warehouse, involved 25 participants from local farmer groups. The results indicate a significant improvement in the farmers' understanding of digital marketing tools, including social media platforms and e-commerce. Participants gained practical skills in content creation, product promotion, and account management. Despite the success, challenges such as limited internet access and device availability were identified as barriers to effective implementation. The training was well-received, with participants expressing high satisfaction with the practical knowledge gained. In conclusion, the digital marketing training was effective in enhancing the farmers' marketing skills, contributing to better product visibility and market reach. However, further support, particularly in infrastructure and continuous training, is necessary to ensure the sustainability of the program and maximize its benefits for the farmers